Analisis Pengaruh Rasio Profitabilitas Terhadap Kebijakan Dividen pada Perusahaan Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2025 - Utama, Rydho; Piter, Jhon; Sisilia, Mariska; Sipahutar, Tetty Tiurma Uli (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of Return on Assets (ROA), Return on Equity (ROE), and Net Interest Margin (NIM) on the Dividend Payout Ratio (DPR) in banking sector companies listed on the Indonesia Stock Exchange for the 2022–2025 period. The study used a quantitative approach with an associative method on 15 companies selected through purposive sampling, resulting in 60 observations. Secondary data in the form of annual financial reports were analyzed using multiple linear regression. The results show that ROA and ROE have a positive effect on DPR, indicating that the higher a bank's ability to generate profits and returns to shareholders, the greater the company's tendency to distribute dividends. Conversely, NIM has no significant effect on DPR, indicating that interest income efficiency is not a primary consideration in dividend distribution policy. Simultaneously, ROA, ROE, and NIM have a significant effect on DPR, with the model explaining 97.2% of the variation in DPR. These findings confirm that profitability is the primary factor influencing dividend policy in banking companies, while intermediation performance reflected through NIM does not directly determine the amount of dividends distributed